2009
DOI: 10.1089/lap.2008.0234
|View full text |Cite
|
Sign up to set email alerts
|

Retroperitoneal Cystic Lymphangioma: A Rare Presentation in Childhood, Treated Laparoscopically

Abstract: Retroperitoneal cystic lymphangioma is a rare benign lesion of childhood. A 15-year-old girl underwent laparoscopic excision of such a cyst. On histopathological examination, the resection was complete. She had an uneventful recovery and remains asymptomatic. We report this in view of the rarity of this condition and also the unusual presentation of this case. Complete surgical excision via laparoscopy is a feasible option.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 6 publications
0
9
0
Order By: Relevance
“…Re-do aortopexy was reported in less than 1% of cases. Other surgical procedures performed before, in association with, or after, aortopexy were; vascular ring division (17.5%), external or internal stenting of the trachea (5%), tracheal resection or tracheoplasty (3.7%), and tracheopexy (1.3%) Three studies reported a predisposition of the patients to get chest infections, even long after aortopexy [11,13,14]. …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Re-do aortopexy was reported in less than 1% of cases. Other surgical procedures performed before, in association with, or after, aortopexy were; vascular ring division (17.5%), external or internal stenting of the trachea (5%), tracheal resection or tracheoplasty (3.7%), and tracheopexy (1.3%) Three studies reported a predisposition of the patients to get chest infections, even long after aortopexy [11,13,14]. …”
Section: Resultsmentioning
confidence: 99%
“…Left anterior thoracotomy can be considered the preferred approach by the vast majority of surgeons (72% of the patients received a left anterior thoracotomy), but up to one third of the patients are treated with other surgical approaches. Thoracoscopy has been used in 1% of cases, belonging to three centres, though apparently with satisfactory results, [4,13,17]. The theoretical advantage of thoracoscopic aortopexy is obviously to reduce the postoperative pain and the morbidity of a thoracotomy or sternotomy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Laparoscopic excision of the retroperitoneal CL in children is rarely reported in the literature (5,9). According to a recent literature review, there are only three reported retroperitoneal CL cases which were successfully excised by laparoscopy in children, but none of them was located in the adrenal region (13).…”
Section: Adrenal Cystic Lymphangiomamentioning
confidence: 99%
“…Surgery for large neonatal abdominal lymphatic malformations has generally required laparotomy [7]. However, in older children, several centers have reported laparoscopic excision [8][9][10]. In neonates, laparoscopic-only approaches appear rare and confined to mesenteric lymphatic malformations [2,[11][12][13].…”
mentioning
confidence: 99%